HUBUNGAN EXSPLOSIVE POWER OTOT LENGAN DAN BAHU TERHADAP HASIL TOLAK PELURU GAYA O’BRIEN SISWA PUTRA KELAS XI MATEMATIKA ILMU ALAM1 MAN 1 MUARA FAJAR PEKANBARU - Syaiful Hidayat; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This problem in this study is still the numbers of students who failed in achieving the target of refulsion that is 6 meters. This study aims is to determine whether there is a corelation of bicep power with the outcome of shot put in orthodox style on a male students of MAN 1 Muara Fajar Pekanbaru. Sample collections tecnique is total sampling the population of this study are a male students of grade XI Mathematics sciens grade in MAN 1 Muara Fajar Pekanbaru, the sample of this study were male students of grade XI Mathematics sciens MAN 1 Muara Fajar Pekanbaru with the numbered of students are 12 students. This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of α = 0.05. Test of normality of variabels X, L0maks (0,128) < Ltabel (0,242), and testing normality of variabels Y, L0maks (0,222) < Ltabel (0,242) in other words at a of normal data and concluded the results showed: there is a significant relationship between eye and food coordination with ability sila kick, with correlation r= 0.646, where rhitung > rtabel or 0.646 > 0,576. and such relations are categorized strong . Thus, Ho rejected and Ha accepted.Key Words: Bicep power with the shot put in o’brien style